FORMULASI TABLET HISAP EKSTRAK ETANOLIK DAUN KEMANGI (Ocimum sanctum L.) DENGAN VARIASI PEMANIS MANITOL DAN LAKTOSA - Devi Nisa Hidayati; Lusyana Setiawati Marwan; Mufrod Mufrod (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACT Holy basil leaves (Ocimum sanctum L.) traditionally used by the people as a stomatitis aphtosa medication. Bacteria could cause stomatitis aphtosa. Flavonoids in holy basil leaves had antibacterial activity. The usage of holy basil leaves traditionally were not practice so formulated more acceptable such lozenges. Acceptability is influenced by a taste. This study aims was to determine sweeteners variations which is mannitol and lactose from the lozenges formulation of holy basil leaves extract on the physical properties and the level of consumer acceptance taste. Holy basil leaves extract made by maceration method using 70% ethanol. Lozenges made within 5 based on the variation concentration of mannitol and lactose are FI (100%:0%), FII (75%:25%), FIII (50%:50%), FIV (25%:75%), dan FV (0%:100%) and manufactured by wet granulation method. The granules obtained were tested for physical properties include flowability, angle of repose, and compressibility. The tablets obtained were tested for physical properties including weight uniformity, hardness, friability, dissolve time, responsive taste test, and the active substance with TLC methods. The data obtained were analyzed statistically using one way ANOVA and Kruskal Wallis, except acceptability taste analyzed descriptionally. The results showed that all formulas provide lozenges which conform the quality specification. Lozenges most accepted by the respondents was formula I. Keywords: holy basil leaves, lozenges, mannitol, lactose